EXPLORING THE RELATIONSHIP BETWEEN GINGIVAL PIGMENTATION AND DENTAL CARIES AMONG STUDENTS IN DIYALA CITY, IRAQ - Shakir Hussain (International Journal of Medical Science and Public Health Research, 2024)
This study investigates the relationship between gingival pigmentation and dental caries among students in Diyala City, Iraq. Gingival pigmentation, a common oral mucosal condition, has been hypothesized to correlate with dental caries susceptibility due to potential differences in oral hygiene practices and dietary habits. A cross-sectional survey was conducted among a sample of students, assessing gingival pigmentation using standardized clinical examination methods and recording dental caries prevalence through visual inspection and radiographic assessment. Statistical analysis, including chi-square tests and logistic regression, was employed to analyze the association between gingival pigmentation and dental caries, adjusting for relevant demographic and oral health variables. The findings indicate a significant association between the presence of gingival pigmentation and higher rates of dental caries among students in Diyala City. These results underscore the importance of further research into the underlying factors contributing to this relationship and the potential implications for preventive dental care strategies.